Light-driven electron injection from a biotinylated triarylamine donor to [Ru(diimine)3]2+-labeled streptavidin. Issue 30 (14th July 2016) - Keller, Sascha G.; Pannwitz, Andrea; Schwizer, Fabian; Klehr, Juliane; Wenger, Oliver S.; Ward, Thomas R.
Abstract : A dyad of covalently anchored [Ru(diimine)3 ] 2+ and a biotinylated triarylamine for the photogeneration of a charge-separated species within streptavidin. Abstract : Electron transfer from a biotinylated electron donor to photochemically generated Ru(iii ) complexes covalently anchored to streptavidin is demonstrated by means of time-resolved laser spectroscopy. Through site-selective mutagenesis, a single cysteine residue was engineered at four different positions on streptavidin, and a Ru(ii ) tris-diimine complex was then bioconjugated to the exposed cysteines. A biotinylated triarylamine electron donor was added to the Ru(ii )-modified streptavidins to afford dyads localized within a streptavidin host. The resulting systems were subjected to electron transfer studies. In some of the explored mutants, the phototriggered electron transfer between triarylamine and Ru(iii ) is complete within 10 ns, thus highlighting the potential of such artificial metalloenzymes to perform photoredox catalysis.